Measuring the Dynamic Characteristics of Electric Motors - Szíki, Gusztáv Áron; Szántó, Attila; Sarvajcz, Kornél (International Journal of Engineering and Management Sciences, 2019)
In our previous publications [1, 2], we described our vehicle dynamics simulation program which was developed in MATLAB environment. We also discussed its use for optimizing the technical parameters of electric driven vehicles. We detailed the model and simulation of the series wound DC motor which is part of the program. Besides, we described the experimental procedure by which we can determine the electromagnetic characteristics of the motor from the input parameters of the simulation program. In the present publication we deal with the determination of the dynamic characteristics of the motor (the moment of inertia of the rotor, bearing and brush resistance torques) experimentally. Knowing the above mentioned electromagnetic and dynamic characteristics, we can carry out the simulation of the motor and the results of the simulation can be compared to the results of the test measurements.